Study on the Effect of Macrophages on Vascular Endothelium in Mice With Different TCM Syndromes of Dyslipidemia and its Biological Basis Based on RNA-Seq Technology - Chen, Jing; Ye, Chao; Yang, Zheng; Wang, Tieshan; Xu, Bing; Li, Pengyang; Zhang, Shan; Xue, Xiaolin (Frontiers in Pharmacology, 2021)
Background: “Treating the same disease with different methods” is a Traditional Chinese medicine (TCM) therapeutic concept suggesting that, while patients may be diagnosed with the same disease, they may also have different syndromes that require distinct drug administrations. Objective: This study aimed to identify the differentially expressed genes and related biological processes in dyslipidemia in relation to phlegm–dampness retention (PDR) syndrome and spleen and kidney Yang deficiency (SKYD) syndrome using transcriptomic analysis. Methods: Ten ApoE−/− mice were used for the establishment of dyslipidemic disease–syndrome models via multifactor-hybrid modeling, with five in the PDR group and five in the SKYD group. Additionally, five C57BL/6J mice were employed as a normal control group. Test model-quality aortic endothelial macrophages in mice were screened using flow cytometry. Transcriptomic analysis was performed for macrophages using RNA-Seq. Results: A quality assessment of the disease–syndrome model showed that levels of lipids significantly increased in the PDR and SKYD groups, compared to the normal control group, p < 0.05. Applying, in addition, hematoxylin and eosin staining of aorta, the disease model was also successfully established. A quality assessment of the syndrome models showed that mice in the PDR group presented with typical manifestations of PDR syndrome, and mice in the SKYD group had related manifestations of SKYD syndrome, indicating that the syndrome models were successfully constructed as well. After comparing the differentially expressed gene expressions in macrophages of the dyslipidemic mice with different syndromes, 4,142 genes were identified with statistical significance, p < 0.05. Gene ontology analysis for the differentially expressed genes showed that the biological process of difference between the PDR group and the SKYD group included both adverse and protective processes. Conclusion: The differentially expressed genes between PDR syndrome and SKYD syndrome indicate different biological mechanisms between the onsets of the two syndromes. They have distinctive biological processes, including adverse and protective processes that correspond to the invasion of pathogenic factors into the body and the fight of healthy Qi against pathogenic factors, respectively, according to TCM theory. Our results provide biological evidence for the TCM principle of “treating the same disease with different treatments.”